If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h + 367 = 285 Reorder the terms: 367 + h = 285 Solving 367 + h = 285 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-367' to each side of the equation. 367 + -367 + h = 285 + -367 Combine like terms: 367 + -367 = 0 0 + h = 285 + -367 h = 285 + -367 Combine like terms: 285 + -367 = -82 h = -82 Simplifying h = -82
| (3x-9)/5=6 | | 2b^2-2b-5=0 | | -8x+1.4=9.4 | | x/1-9=-9 | | (5x-6)(x+10)=0 | | 75q=3756 | | -6x-6-7=-13 | | -2(x-9)=-34 | | 8b=96 | | 4k-5k-4k= | | 17g=981 | | 4x^3-2x^3= | | -5=q^7 | | 30=12x-4+10x-10 | | -14x=-336 | | 3x-9/5=6 | | .75z+6= | | 3(y-4)=(3y-5-4y)-(2-5y+10) | | 6.6g+4=4.6g+8 | | 75=3x+2+10x-5 | | 1/3-4/x=2-3/2x | | 7x-10+28+2x=-5 | | 5b=2.000 | | Y=2x^4+18x^3+40x^2+24x | | y+708=1179 | | (6gk)/(3k^2) | | 2w-3= | | 1/6/54 | | 6gk/3k^2 | | 234+y=123 | | 102=6y | | 8m+3(n+7m)-n= |